REVIVING THE WASATIYYAH VALUES FOR INTER-RELIGIOUS HARMONY IN PLURAL SOCIETIES - Syihab, Abdul Halim; Muhamad, Asmawati (Journal of Al-Tamaddun, 2017)
World religions play an important key role in sustaining interreligious harmony between the different creeds and cultures of humanity. Therefore, it is very imperative for every adherents of major religions to uphold and practice the essential values of their religious teachings consistently. As for Islam, it has rich tradition of guiding principles, called wasatiyyah that ensures the social justice and prosperity in a plural society. This article aims at reviving the pertinent values of wasatiyyah concept that has been practiced by the early generations of Muslim society. For this purpose, we have reviewed major works of Islamic literature and applied content analysis of these resources. Current example of Malay world is taken into portion as a model of wasatiyyah society. It is found that wasatiyyah values provide vital elements of balance, justice, excellent, strength, honour, and peace that would give significant impact in building inter-religious harmony among world community. Indeed, an empirical work of wasatiyyah application should be further pursued in order to fully justify its workable methods of instrumenting the positive values of wasatiyyah in the current context of plural societies.